2021
DOI: 10.1002/jts.22728
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Traumatic Events and the Association Between Gender Minority Stress and Suicide Risk in a Gender‐Diverse Sample

Abstract: Transgender and gender diverse (TGD) individuals are at an elevated risk of trauma exposure and other negative mental and physical health outcomes. The present study examined the interaction between minority stressors, reported potentially traumatic events (PTEs), and suicide risk (i.e., ideation and behavior) in a TGD sample. A convenience sample of 155 self‐identified TGD individuals completed questionnaires assessing distal (e.g., gender‐related discrimination) and proximal (e.g., internalized transphobia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…This finding could suggest that if TGNC individuals had experienced abuse specific to their transgender identity, they may have expected that they would also be treated poorly by other people due to their identity; these negative expectations may have then contributed to the development of mental health symptomatology. This finding is consistent with past research that found that proximal stressors were the mechanism by which distal stressors related to mental health (Cogan et al, 2021;Jäggi et al, 2018), as well as one study finding that negative expectations specifically explained the relationship between rejection, nonaffirmation, and victimization and suicidal ideation (Testa et al, 2017). Furthermore, the findings of the present study are consistent with prior research demonstrating that negative expectations were associated with both depression (Hidalgo et al, 2019;Testa et al, 2015;Timmins et al, 2017) and anxiety (Chodzen et al, 2019;Timmins et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding could suggest that if TGNC individuals had experienced abuse specific to their transgender identity, they may have expected that they would also be treated poorly by other people due to their identity; these negative expectations may have then contributed to the development of mental health symptomatology. This finding is consistent with past research that found that proximal stressors were the mechanism by which distal stressors related to mental health (Cogan et al, 2021;Jäggi et al, 2018), as well as one study finding that negative expectations specifically explained the relationship between rejection, nonaffirmation, and victimization and suicidal ideation (Testa et al, 2017). Furthermore, the findings of the present study are consistent with prior research demonstrating that negative expectations were associated with both depression (Hidalgo et al, 2019;Testa et al, 2015;Timmins et al, 2017) and anxiety (Chodzen et al, 2019;Timmins et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Hendricks and Testa (2012) later applied the Minority Stress Model to the TGNC population, creating the Gender Minority Stress Model. Several studies have found support for this model; for example, proximal stressors have been found to mediate the relationship between distal stressors and depression (Jäggi et al, 2018) and suicide risk (Cogan et al, 2021) in TGNC samples. However, more research is needed to test pathways among specific distal stressors, proximal stressors, and mental health outcomes (Valentine & Shipherd, 2018).…”
Section: The Gender Minority Stress Modelmentioning
confidence: 93%
“…A critical review of the literature Susana Merino-Lorente understanding, control, and belonging, with deleterious effects on mental health. Furthermore, trauma and discrimination, whether acute or chronic, produce heightened stress responses, including avoidance of stimuli associated with the traumatic or discriminatory event and hypervigilance (anticipatory stress) about the possibility of future trauma or discrimination), as well as similar physiological responses in reaction to acute laboratory stressors (Cogan et al, 2021). There is evidence that exposure to traumatic stress and stigma-related stress operate through similar minority stress processes (Meyer, 2020), Minority stress theory (Meyer, 2020) have proportioned an essential framework for understanding mental health differences among gender minorities.…”
Section: Methodsmentioning
confidence: 99%
“…These different episodes, along with common stressors, extremely affect the mental health and well-being of TBN people. An extension of this work also focuses on how individual internal sociopsychological processes (eg, appraisal, coping, and emotion regulation) mediate the association between stressful experiences and minority sociopsychology (Cogan et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation